Combating vaccine hesitancy: The case of HPV vaccination - Lina Díaz; Deborah Martínez Villarreal; Karina Márquez; Carlos G. Scartascini (Inter-American Development Bank (IDB), 2025)
Cervical cancer, primarily caused by persistent Human Papillomavirus (HPV) infection, remains one of the leading causes of cancer-related deaths among women in developing countries. Although HPV vaccines are widely available in these regions, vaccine uptake remains persistently low. To address behavioral barriers contributing to this low demand, we evaluated the effectiveness of a behaviorally informed SMS campaign targeting parents in Cali, Colombia. Our study included 15,231 parents, who were randomized into six groups: control, placebo, and four behaviorally informed treatment groups, forming a large-scale study of text-based nudges. Participants received tailored messages over eight weeks. The intervention yielded significant increases in vaccination rates, with improvements ranging from 34% to 55%. Furthermore, the economic analysis demonstrated that the intervention generated between USD 3.6 and USD 5.75 in economic benefits for every dollar spent, primarily due to prevented deaths. These findings underscore the potential of behavioral interventions in enhancing HPV vaccination rates among parents and emphasize the cost-effectiveness and relative success of each intervention strategy. This study provides actionable insights for public health officials to design targeted strategies that address vaccination disparities and promote preventive healthcare practices.
Keywords: D01; I12; 330; Vaccination; HPV vaccine; Behavioral science